Social Event Memory Test (SEMT): A Video-based Memory Test for Predicting Amyloid Positivity for Alzheimer's Disease - Kim, Ko Woon; Choi, Jong Doo; Lee, Hyejoo; Lee, Na Kyung; Park, Seongbeom; Chin, Juhee; Lee, Byung Hwa; Shin, Jiwon; Kim, Yeshin; Jang, Hyemin; Choi, Jee Hyun; Na, Duk L. (NATURE PUBLISHING GROUP, 2018)
Recent improvements in neuroimaging and molecular markers of Alzheimer's disease (AD) have aided diagnosis in the early stage of the disease, which greatly increases the chance for successful prevention and treatment. However, the expanding resources for AD diagnosis are unlikely to benefit all elderly due to economic burden. Here, we aimed to develop an inexpensive and sensitive method to detect early-stage AD. A scenario for real-world social event memory test (SEMT) was created and filmed in 360 degrees video. Participants watched the 7-min video through head-mounted display (HMD) and then answered questionnaire about the video. We categorized the SEMT score into recall, recognition, and place-matching scores and compared them to scores on the Mini-Mental State Examination and Seoul Verbal Learning Test. Using the SEMT scores, we built a logistic regression model that discriminated between amyloid positivity and negativity of the participants, with a cross-validation AUC. Furthermore, a classifier was created using support vector machine, which produced 93.8-95.1% sensitivity in classifying individuals into four groups of normal, mild cognitive impairment with or without amyloid, and AD elderly. The high correlation between the SEMT score and amyloid positivity in individuals who experienced virtual social gathering through an HMD opens a new possibility for early diagnosis of AD.
Keywords: MILD COGNITIVE IMPAIRMENT; SUPPORT VECTOR MACHINE; NORMAL OLDER-ADULTS; NEUROPSYCHOLOGICAL ASSESSMENT; HIPPOCAMPAL ATROPHY; MRI; PET